Endohedral Fullerenes: Electron Transfer and Spin - Popov, Alexey A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book discusses recent progress in endohedral fullerenes - their production and separation techniques, as well as their characterization and properties. Furthermore, the book delves into the all-important issue of stability by investigating electron transfer between the encapsulated metal species and the carbon cage. It also reviews spin-based phenomena caused by the shielding of endohedral spin by the fullerene, and analyzes formation of the spin states by charge transfer as studied by electron spin resonance. Tuning of charge states of endohedral species and of spin states of both the cage and the cluster are explained. Finally, the book considers the recent discovery of magnetism in some endohedral fullerenes, and the potential for quantum computing.
From the Contents: Endohedral Metallofullerenes: an overview -- Electron Transfer in Solution -- Ions of Endohedral Fullerenes in the Gas Phase -- Electron Transfer in Solid State -- Scanning Tunneling Microscopy of Endohedral Fullerenes.
Keywords: Nanotechnology; Electrochemistry; Condensed matter; Inorganic chemistry; Organometallic chemistry .; Nanotechnology; Electrochemistry; Condensed Matter Physics; Inorganic Chemistry; Organometallic Chemistry